2022
DOI: 10.1142/s0218127422500286
|View full text |Cite
|
Sign up to set email alerts
|

Infinitely Many Necklace-Shaped Coexisting Attractors in a Nonautonomous Memcapacitive Oscillator

Abstract: Extreme multistability usually emerges in a mem-element’s circuit or system that possesses a line or plane equilibrium set closely associated with the internal initial state of the mem-element. To extend the investigation of extreme multistability, this paper proposes a nonautonomous memcapacitive oscillator, discovering a new type of extreme multistability due to the infinitely many discrete equilibrium points therein. This memcapacitive oscillator is constructed by connecting a simple memcapacitor-resistor c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…This is the main reason that extreme multistability is often discovered in some circuits and systems involving memory-circuit elements. Intriguingly, extreme multistability has also been discovered in some non-autonomous memristive circuits and systems that have time-varying equilibria [33][34][35][36]. For example, a non-autonomous memristive FitzHugh−Nagumo circuit with its equilibrium points transitioning between no equilibrium point and a line equilibrium set was built, and hidden extreme mulitstability was disclosed [34].…”
Section: Introductionmentioning
confidence: 99%
“…This is the main reason that extreme multistability is often discovered in some circuits and systems involving memory-circuit elements. Intriguingly, extreme multistability has also been discovered in some non-autonomous memristive circuits and systems that have time-varying equilibria [33][34][35][36]. For example, a non-autonomous memristive FitzHugh−Nagumo circuit with its equilibrium points transitioning between no equilibrium point and a line equilibrium set was built, and hidden extreme mulitstability was disclosed [34].…”
Section: Introductionmentioning
confidence: 99%
“…Multistability is a situation in which a nonlinear system display several coexisting states for fixed set of system parameters but starting from different initial conditions [22,23]. Since its discovery by Arecchi et al [24], it has been reported in several biological [25], mechanical [26] and electronic [27] systems. Although no work up to date has clearly established its generation mechanism, various methods can be found throughout the literature for characterizing it.…”
Section: Introductionmentioning
confidence: 99%